AN ANALYSIS OF NUTRITIONAL HABITS AMONG YOUNG HUNGARIAN ADOLESCENTS - Kárai, Brigitta; Hidvégi, Péter (Stadium - Hungarian Journal of Sport Sciences, 2020)
In Hungary, malnutrition within the unhealthy lifestyle is one of the main reasons for the high morbidity and mortality rate. In most cases, these attitudes develop in childhood; that is why it is important to feed children properly and educate them to lead a healthy lifestyle. The quantity and quality of meals also affect growth, development, and future health. Improper eating habits play a significant role in developing cardiovascular disease, hypertension, diabetes, and many cancers. Our goal is to explore the areas where students are most accessible, and prevention programs could reduce the proportion of obese youth, and at the same time, obese adults in the future.